Yin Yang 1 promotes the Warburg effect and tumorigenesis via glucose transporter GLUT3. Issue 8 (12th July 2018) - Wang, Yali; Wu, Shourong; Huang, Can; Li, Yanjun; Zhao, Hezhao; Kasim, Vivi
Abstract : Cancer cells typically shift their metabolism to aerobic glycolysis to fulfill the demand of energy and macromolecules to support their proliferation. Glucose transporter (GLUT) family‐mediated glucose transport is the pacesetter of aerobic glycolysis and, thus, is critical for tumor cell metabolism. Yin Yang 1 (YY1) is an oncogene crucial for tumorigenesis; however, its role in tumor cell glucose metabolism remains unclear. Here, we revealed that YY1 activates GLUT3 transcription by directly binding to its promoter and, concomitantly, enhances tumor cell aerobic glycolysis. This regulatory effect of YY1 on glucose entry into the cells is critical for YY1‐induced tumor cell proliferation and tumorigenesis. Intriguingly, YY1 regulation of GLUT3 expression, and, subsequently, of tumor cell aerobic glycolysis and tumorigenesis, occurs p53‐independently. Our results also showed that clinical drug oxaliplatin suppresses colon carcinoma cell proliferation by inhibiting the YY1/GLUT3 axis. Together, these results link YY1's tumorigenic potential with the critical first step of aerobic glycolysis. Thus, our novel findings not only provide new insights into the complex role of YY1 in tumorigenesis but also indicate the potential of YY1 as a target for cancer therapy irrespective of the p53 status. Abstract : We unraveled a novel role of YY1 in enhancing the transcriptional activity of glucose transporter GLUT3 in a p53‐independent manner. This regulation subsequently enhances the glucose uptake into the cells and alters tumor cell metabolism toward glycolysis both in the presence and in the absence of p53. Our findings link the oncogenic characteristic of YY1 with the first, pacesetter step of Warburg glycolysis, and, thus, provide strong evidence for the critical function of YY1 in tumorigenesis, and highlight its potential as a target for treating cancers irrespective of the p53 status.